Determinación del efecto de la deficiencia de vitamina A sobre la homeostasis del hierro y su estado en modelo murino (2020)
Iron deficiency anemia (IDA) and vitamin A deficiency (VAD) belong to the micronutrient deficiencies defined by the WHO as worldwide concern. In Colombia, IDA prevalence for children from 1 to 4 years old is 14.8% and anemia is 24.7% for children from 6 to 59 months old, it is remarkable in a country where is mandatory to fortify wheat flour with iron since 1996. On the other hand, VAD prevalence for children from 1 to 4 years old is 27.3% and, in this case, there is no mandatory fortification programs in the country. Interactions between micronutrients are not unknown on health and nutrition field, the most recognized is that between calcium and vitamin D; besides, there is evidence from an epidemiological perspective that VAD and ID are linked in some way, fact supported for some studies using cellular and animal models. This study has the hypothesis that vitamin A regulates in some way the iron homeostasis and its metabolic role, and has three approaches: weight gain, biochemical and hematological parameters and molecular markers of iron homeostasis. We designed a study with four experimental diets with different ratios of iron and vitamin A (sufficient, insufficient and deficient) and a control diet with a sufficient supply of both micronutrients. The quantity of animals was calculated statistically giving seven animals per group for 35 animals. The rats started the experiment at weaning (21 days-old) and received food and water at libitum for six weeks, during this time food intake and weight were recorded each week. At sixth week the animals were euthanized and samples from blood and tissues of interest (liver, spleen and duodenum) were taken for analysis of biochemical and hematological indicators in blood and PCR and Western Blot test in tissues for the analysis of hepcidin, ferritin, transferrin receptors, transferrin and interleukin-6 as proteins of interest.